Floristic survey of vascular plants of the Parque Estadual da Pedra Selada, Rio de Janeiro, Brazil - Waga, Isabela Maciel; Costa, Andrea Ferreira da; Mynssen, Claudine Massi; Fernandez, Eduardo Pinheiro; Guimarães, Elsie Franklin; Saleme, Fernanda; Queiroz, George Azevedo de; Antar, Guilherme Medeiros; Lima, Haroldo Cavalcante de; Marques, Hemily Oliveira; Deccache, Lara Serpa Jaegge; Cardoso, Leandro Jorge Telles; et al. (Pensoft Publishers, 2024)
Background The Atlantic Forest is one of the most diverse and threatened phytogeographical domains in the world. Despite that, it includes regions with poor floristic knowledge, even in protected areas. Although the importance of protected areas in conserving the Atlantic Forest hotspot is undisputed, it is necessary to recognise the floristic richness of these areas to propose effective conservation actions. In this sense, online databases have proved to be a promising tool for compiling species lists with relevant biodiversity information. This study is based on the list of vascular plants of the “Parque Estadual da Pedra Selada”, published in the “Catálogo de Plantas das Unidades de Conservação do Brasil”. It summarises the species richness, endemism and conservation status of this protected area. New information The published list of vascular plants was based on data obtained from herbarium collections available in online databases. A total of 303 species have been recorded for the “Parque Estadual da Pedra Selada, ” of which 297 are native to Brazil, 78 are endemic to the Brazilian Atlantic Forest, and seven are endemic to the State of Rio de Janeiro. More than 60% of the species are woody, and more than 40% are trees. Eight threatened species (Endangered – EN and Vulnerable – VU), of which five are endemic to the State of Rio de Janeiro, are housed in this protected area. One species was classified as Data Deficient (DD). Our results increase the knowledge of the Atlantic Forest flora in the State of Rio de Janeiro and support effective conservation planning for this protected area.
Keywords: Atlantic Forest; conservation; endemism; plant richness; threatened species